Shared Space in Distance: A Phenomenological Study on Student Leadership in Virtual Platform - Wilter C. Friales (CV. Literasi Indonesia, 2021)
Campus student leadership in a virtual space refers to the pursuit of student leaders in pursuing leadership through organizing, implementing, and facilitating programs and activities virtually. This study utilized a Qualitative Transcendental Phenomenological approach with two sets of focused group discussions and two in-depth interviews. Four themes (categories) emerged that characterized the essence (structure) of the phenomenon of student leadership in virtual space. The themes include “transition and gains” that discuss their experience of the shift from face-to-face leadership to the virtual platform. The second theme is “Mindfulness and Actions” which describes how their mental attitudes have changed when it comes to making decisions now that they lead virtually. The third one is “Adaptability and Coping” which discusses their experiences on how they adapt to the changes and cope with the challenges. The fourth theme is on “virtual rapport and connection” which explains the roles exemplified by the student leaders in establishing the connections among them in the virtual space. The understanding of student leadership in a virtual space provides input for the institution in intensifying its support and improving the delivery of virtual programs and activities through more effective and efficient leadership of students.